2019
DOI: 10.3847/1538-4357/ab1b1c
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Red and Dusty Ultraluminous X-Ray Sources with Spitzer

Abstract: We present a mid-infrared (IR) sample study of nearby ultraluminous X-ray sources (ULXs) using multi-epoch observations with the Infrared Array Camera (IRAC) on the Spitzer Space Telescope. Spitzer /IRAC observations taken after 2014 were obtained as part of the Spitzer Infrared Intensive Transients Survey (SPIRITS). Our sample includes 96 ULXs located within 10 Mpc. Of the 96 ULXs, 12 have candidate counterparts consistent with absolute mid-IR magnitudes of supergiants, and 16 counterparts exceeded the mid-IR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 160 publications
(196 reference statements)
6
22
0
Order By: Relevance
“…The broadband spectrum can only be fit by adding two extra components, a blue component that domi-nates the emission bluewards of ∼ 700 nm and a red component that dominates the K-band emission. The excess red emission is also observed in Spitzer observations (Lau et al 2016(Lau et al , 2019 and is consistent with being due to warm dust with a temperature of ∼ 1100 K. The presence of excess blue emission is consistent with predictions from theory (e.g., Copperwheat et al 2005;Ambrosi & Zampieri 2018), and is likely due to an irradiated accretion disc and/or irradiation of the donor star by the bright X-ray source. The strong variability of NGC 300 ULX-1 in X-rays indicates that this component, if it is indeed due to reprocessed Xray emission, may be variable as well.…”
Section: Additional Broadband Componentssupporting
confidence: 87%
“…The broadband spectrum can only be fit by adding two extra components, a blue component that domi-nates the emission bluewards of ∼ 700 nm and a red component that dominates the K-band emission. The excess red emission is also observed in Spitzer observations (Lau et al 2016(Lau et al , 2019 and is consistent with being due to warm dust with a temperature of ∼ 1100 K. The presence of excess blue emission is consistent with predictions from theory (e.g., Copperwheat et al 2005;Ambrosi & Zampieri 2018), and is likely due to an irradiated accretion disc and/or irradiation of the donor star by the bright X-ray source. The strong variability of NGC 300 ULX-1 in X-rays indicates that this component, if it is indeed due to reprocessed Xray emission, may be variable as well.…”
Section: Additional Broadband Componentssupporting
confidence: 87%
“…This means that, at the time of writing this manuscript, the photometric and spectroscopic observations provided 3 confirmed RSGs, 12 candidate RSGs, 4 confirmed nebulae, and 14 candidate stellar clusters/active galactic nuclei (AGNs). Recently, Lau et al (2019) observed 96 ULXs within 10 Mpc in the mid-IR with the Spitzer Space Telescope. They detected and identified 12 ULXs with candidate counterparts whose absolute mid-IR magnitude is consistent with being RSGs.…”
mentioning
confidence: 99%
“…RSG donors exist outside our Galaxy as well. Lau et al (2019) searched for Spitzer/IRAC mid-IR counterparts of ultraluminious X-ray sources (ULXs), which are thought to be X-ray binaries with luminosities equal to or above the Eddington luminosity of a stellar-mass black hole. This luminosity is powered by accretion onto a compact object.…”
Section: Does Xid 6592 Really Contain An Rsg Donor?mentioning
confidence: 99%
“…This luminosity is powered by accretion onto a compact object. Lau et al (2019) found 12 counterparts with SG-like fluxes, where 4 sources were "red" ([3.6]-[4.5]∼0.7) and 5 were "blue" ([3.6]-[4.5]∼0) based on the IRAC colors. These correspond to sgB[e] and RSG companions, respectively.…”
Section: Does Xid 6592 Really Contain An Rsg Donor?mentioning
confidence: 99%